Proceso de atención de enfermería en neonato con síndrome de abstinencia neonatal, área de CIN Hospital Universitario de Guayaquil. - Bonilla Villa, Mónica Susana (2020)
Neonatalabstinence syndrome is the set of physical and psychological disorders that presents those who have already developed dependence on a drug, when it suspends its consumption abruptly, or decreases it significantly after a prolonged period of ingestion,neonatal withdrawal syndrome is the main complication that suffers from the children of intoxicant mothers, because the pregnant woman interrupts the type of substance that produces the neonate, this develops withdrawal syndrome and may exhibit early signs such as the reflex of the decreased APGAR of the newborn, clinical manifestations by heroin, diagnosis in neonatal abstinence The clinical manifestations of neonatal withdrawal syndrome change depending on the type of components involved. If the duration stage between maternal use of the drug and childbirth is greater than 1 week, the probability of neonatal withdrawal is lower. Anewborn is a child who is less than 28 days old. These 28 days of life are the ones that carry the highest risk of death for the child. Immediate attention to the newborn is very important and requires special nursing procedures, the transfer of the newborn to the extrauterine environment is a sudden and full of changes so it is important to treat it with as much care as possible. For the nursing professional it is very important to apply the nursing care process which will help us to perform a systematic and organized method in order to provide individualized care to each person, applying skills, skills acquired correctly since each patient responds differently to an alteration whether real or potential. The overall goal in this clinical case is to fold the nursing care process into neonate with neonatal withdrawal syndrome.